Gene-environment interactions in antisocial behavior are mediated by early-life 5-HT2A receptor activation. (15th November 2019) - Godar, Sean C.; Mosher, Laura J.; Scheggi, Simona; Devoto, Paola; Moench, Kelly M.; Strathman, Hunter J.; Jones, Cori M.; Frau, Roberto; Melis, Miriam; Gambarana, Carla; Wilkinson, Brent; DeMontis, M. Graziella; et al.
Abstract: The ontogeny of antisocial behavior (ASB) is rooted in complex gene-environment (G×E) interactions. The best-characterized of these interplays occurs between: a) low-activity alleles of the gene encoding monoamine oxidase A ( MAOA ), the main serotonin-degrading enzyme; and b) child maltreatment. The purpose of this study was to develop the first animal model of this G×E interaction, to help understand the neurobiological mechanisms of ASB and identify novel targets for its therapy. Maoa hypomorphic transgenic mice were exposed to an early-life stress regimen consisting of maternal separation and daily intraperitoneal saline injections and were then compared with their wild-type and non-stressed controls for ASB-related neurobehavioral phenotypes. Maoa hypomorphic mice subjected to stress from postnatal day (PND) 1 through 7 – but not during the second postnatal week - developed overt aggression, social deficits and abnormal stress responses from the fourth week onwards. On PND 8, these mice exhibited low resting heart rate - a well-established premorbid sign of ASB – and a significant and selective up-regulation of serotonin 5-HT2A receptors in the prefrontal cortex. Notably, both aggression and neonatal bradycardia were rescued by the 5-HT2 receptor antagonist ketanserin (1–3 mg kg −1, IP), as well as the selective 5-HT2A receptor blocker MDL-100, 907 (volinanserin, 0.1–0.3 mg kg −1, IP) throughout the first postnatal week. These findings provide the first evidence of a molecular basis of G×E interactions in ASB and point to early-life 5-HT2A receptor activation as a key mechanism for the ontogeny of this condition. This article is part of the Special Issue entitled 'The neuropharmacology of social behavior: from bench to bedside'. Highlights: Antisocial behavior (ASB) is predisposed by gene x environment interactions (GEIs). The best-known GEI occurs between low-activity MAOA alleles and child maltreatment. We developed the first mouse model of this GEI and studied its underlying mechanism. MAOA-hypomorphic mice subjected to early-life stress develop ASB-related phenotypes. Our data suggest that this GEI is mediated by 5-HT2A receptors.